Approach to the development of a frailty index based on comprehensive geriatric assessment in nursing home - Juan Francisco Peris-Martí; Mª Ángeles Parro Martín; Elia Fernández-Villalba; Patricia Bravo José (Farmacia Hospitalaria)
Objective: To carry out an approach for the development of a frailty index in nursing homes and to analize its potential use in order to individualize the pharmacological treatment. Method: The frailty index was constructed from the information included in the comprehensive geriatric assessment established in nursing homes. The index has been retrospectively applied to the patients of two centers using the last comprehensive geriatric assessment of each one. Results: 17 variables that included 27 deficits were selected and classified in 4 domains. 269 patients (mean age 82.9 ± 8.8 years) were included in the analysis. The frailty index indicated that 86% of patients should be considered frail and 60% of these to moderate-advanced level. Conclusions: The frailty index is simple and quick to apply. It seems to have discriminative capacity in terms of quantifying the degree of frailty and it could be useful in prescribing the most appropriate therapeutic aggressiveness to each patient.